KONTEKSTUALISASI HUKUM WARIS DI INDONESIA DALAM PERSPEKTIF AL-QUR’AN DAN HADIS - Suryaman, Ujang; Sadari, Sadari; Hadi, Abdul; Mujiono, Mujiono; Bahruddin, Ah (Moderation | Journal of Islamic Studies Review, 2024)
Everyone will experience the process of mutual inheritance. During the distribution of inheritance, sometimes there are many disputes or disputes between heirs. Problems arise because they feel that there is no justice or because there is a lack of understanding of this problem. In Indonesia, there are three types of inheritance law systems, namely Islamic inheritance law, customary inheritance law and burgerlijk wetboek (BW) civil inheritance law. This research aims to find out how the Qur'an and Hadith view the inheritance law system prevailing in Indonesia and the importance of Muslims to take a system that is in accordance with the Qur'an and Hadith. This research method uses a qualitative approach with the type of literature research (liberary research). Qualitative research is research that is descriptive and tends to use analysis. The analyses used are inductive analysis, deductive analysis and comparative analysis. The results of this research are very important for implementing Islamic inheritance law, because it is obedience to Allah in the Qur'an and Hadith. The Islamic inheritance system that applies in Indonesia is based on the Islamic Law Compilation (KHI) guidebook which has been adapted to the Qur'an and Hadith and the fiqh book of scholars. Settlement of inheritance disputes for Muslims can only be resolved at the Religious Court in accordance with Law Number 3 of 2006 as amended by Law Number 7 of 1989. The civil inheritance legal system in Indonesia is only intended for non-Muslim citizens.